Enhanced Hydrothermal Resistance of Y‐TZP Ceramics Through Colloidal Processing. Issue 4 (28th February 2013) - Rayón, E.; Moreno, R.; Alcázar, C.; Salvador, M. D.; Manjón, F.J.; Jiménez‐Piqué, E.; LLanes, L.
Abstract : Two commercial zirconia powders with 3 mol% of yttria (TZ3YE and TZ3YS, labeled as ZE and ZS, respectively) supplied by Tosoh (Japan) were used for this study. Maximum colloidal stability for ZE was achieved by dispersing the powders in a mixture of water/ethanol of 90:10 (wt/wt) using a sonication probe. The rheological behavior of the suspensions was optimized in terms of solids content ranging from 20 to 33 vol% and sonication time (0–6 min), the best results being obtained after 2 min. ZS samples were prepared to a solids loading of 30 vol% in water dispersing with 2 min‐sonication. Samples obtained by slip casting in plaster molds were used for dynamic sintering studies, and fully dense and nanostructured specimens were obtained at temperatures of 1300°C–1350°C (ZE samples) and 1400°C per 2 h (ZS samples). The Hardness ( H ) and Young's Modulus ( E ) properties of the specimens were studied by nanoindentation technique giving 17 and 250 GPa mean values for H and E, respectively. The specimens were then forced to a low‐temperature degradation (LTD) treatment at 130°C for 240 h in steps of 60 h. Raman spectroscopy and nanoindentation results of hydrothermally treated samples showed the absence of transformation from tetragonal to monoclinic phase until 180 h whereas the mechanical properties maintained constant even at the sample surface. After 240 h of LTD, the monoclinic phase was detected on all specimens by Raman peaks centered at 180, 191, and 383 cm −1 . The nanoindentation study revealed an important loss of mechanical features reaching 10 and 175 GPa for H and E, respectively. In the case of the ZS specimens, no monoclinic phase is detected after 240 h of LTD treatment and no decay of E or H is detected. The free defect microstructure reached for the ZS specimen revealed a higher hydrothermal resistance so that it is concluded that the excellent behavior against thermal degradation is possible due to the large uniformity obtained by colloidal processing rather than the particle size of the starting powders.